Antibiogram Pattern of Uropathogenic Escherichia Coli in Baghdad Province, Iraq - Nuha Abd Al.rheem Saad; Raghad Hassan Hussein; Nadia M.M. Al-Shakir (Journal of Techniques)
Uropathogenic Escherichia coli (UPEC) is considered one of the main causes of urinary tract infections. Antimicrobial resistance (AMR) is a significant global health care issue, particularly with regard to urinary tract infections. Objective: To evaluate the prevalence of antibiotic resistance among Escherichia coli isolated from patients with urinary tract infection.